TEACHING VOCABULARY THROUGH INTERACTIVE VOCABULARY TECHNIQUE - Sri, Rahayu (Institut Agama Islam Negeri Palopo, 2015)
The objective of this research were to find out whether or not (1) the use of interactive vocabulary technique improved studentsâ English vocabulary and (2) students are interested in learning vocabulary using interactive vocabulary technique.This research applied quasi experimental method. The subject of the research was the second year students of SMP Negeri 3 Palopo, academic year 2011/2012. The sample consisted of two classed of two classes, they are control group and experimental group. They were trained through interactive vocabulary technique and coventional technique. While questionnaire was used to collect data of studentsâ interest in learning vocabulary using interactive vocabulary technique.The result of data analysis showed that the studentsâ achievement in experimental group and control group were significantly different. It was proved by the mean score of the students posttest in the experimental group is 7.94 which was greater than the mean score of the studentsâ posstest in the control group is 6,84. The data analysis from questionnaire also showed that the degree of the studentsâ interest was very high. Based on the data analysis, the research concluded that the studentâ vocabulary improved significantly by the use of interactive vocabulary technique. The use of interactive vocabulary technique was interesting to the students, so they were motivated to learn English Vocabulary.